The overview of nurses' performance in low-birth-weight care in agricultural areas - Abdulloh Faqih S. M.; Ira Rahmawati; Peni Perdani Juliningrum; Lantin Sulistyorini (Nursing and Health Sciences Journal (NHSJ), 2025)
Low birth weight (LBW) infants represent the second leading cause of neonatal mortality in Indonesia. These infants require intensive care after hospital discharge but are often readmitted due to dehydration, fever, respiratory distress, diarrhea, and vomiting conditions linked to families' inadequate preparedness for home care. Nurses play a critical role in LBW care, delivering promotive, preventive, curative, and rehabilitative services through a nursing process that addresses individuals, families, and groups. Enhancing nursing performance in LBW care necessitates the support of health workers and cadres. This support is best implemented through maternal and child health programs focused on preparation, implementation, assistance, monitoring, and evaluation for families managing low birth weight infants. Method: This study employed a descriptive quantitative design, targeting nurses who had managed low birth weight (LBW) infants in the Agricultural Health Center (Puskesmas) Ajung, Sumbersari, Rambipuji, Panti, and Kalisat. A total of 68 nurses were sampled using total sampling with a cross-sectional approach, utilizing a modified Multisource Feedback (MSF) Questionnaire as the research instrument. Results Respondents were aged 20-30 years (13.2%), 31-40 years (42.6%), 41-50 years (33.8%), and >51 years (10.3%). Most held a diploma (69.1%), while 30.9% had a bachelor's degree in nursing (News). Nurse performance in managing LBW infants and home visits was rated good in 63.2% of cases, low in 19.1%, and moderate in 17.6%. Most respondents were aged 31-40 years and held a diploma in nursing. Based on frequency and percentage distribution, 63.2% of nurses performed well.